A Conceptual Hybrid Model for Transcultural Product Design Innovation - Yussif Iddrisu; Rui Oliveira Lopes (Wacana Seni Journal of Arts Discourse, 2025)
In the current era of globalisation, cultural diversity is playing a critical role in shaping how individuals interpret, exchange, or adopt sociocultural traits from other cultures. In this context, creating a transcultural product has become a complex process that demands a keen understanding of user identity and cultural differences. The primary aim of this study is to develop a hybrid framework for designing culturally inclusive transcultural products. To achieve this goal, we have consolidated selected models of cultural and cross-cultural product design innovation. A systematic review of these models was conducted using reproducible research practices, following the PRISMA guidelines, to ensure a valid and reliable account of the existing literature. In conclusion, our study offers valuable insights into the intricate process of designing transcultural products, providing designers with a hybridised framework to create culturally inclusive products. This hybridised framework is a significant step towards transcultural product design innovation, and it has the potential to assist in the creation of products that cater to the needs of diverse cultural audiences.